(untitled) (Perner’s Contacts, 2011)
The article describes one of the analytical tools of an application used for train paths ordering by railway undertakings in the Czech Republic. The application is part of the information system for annual train timetable design. It is distributed application composed of database server, application server and client program. The tool allows calculation of many indicators for the freight and passenger transport needs. The calculation can be performed for selected routes, areas, tractions and period. The areas can be standard (the Czech Republic and its regions) as well as user-defined (arbitrary set of transport points and sections). The other parameters can influence the selection of train paths sections, which will be included in the calculation. After the calculation selected train paths can be excluded or included causing immediate recalculation of results.